The Role of Parkinson's Disease Gene PTEN-Induced Putative Kinase 1, PINK1 in Ischemia Induced Neuronal Injury - Safarpour, Farzaneh (Université d'Ottawa / University of Ottawa, 2016)
Stroke results from disturbance in blood flow to an area of the brain, leading to neuronal dysfunction and loss. Mitochondrial dysfunction and oxidative stress are critical factors in neuropathology of stroke. They have also been implicated in Parkinson's disease (PD). Select cases of PD are caused by homozygous mutations in the PINK1 gene. Critically, this gene works with another PD gene, Parkin, to regulate mitochondrial quality control (MQC) mechanisms. Additionally, initial studies of the PINK1 protein have suggested that it plays a critical role in cellular pro-survival responses to oxidative stress though the mechanism by which it does so is unclear. In this dissertation, I explored the potential mechanisms through which PINK1 confers neuroprotection, particularly in the case of ischemic insult. I found that PINK1 deficiency sensitizes neurons to glutamate-induced excitotoxicity. I also found that the PINK1 kinase domain, but not the mitochondrial targeting motif, is essential for its protective effect. Additionally, PINK1 or Parkin deficiency significantly increases the infarct volume after middle cerebral artery occlusion, in vivo. Importantly, expression of Parkin reduces the sensitivity of neurons to cytotoxicity induced by PINK1 deficiency indicating that Parkin functionally interacts with PINK1 either through the same or on parallel survival pathways. Moreover, I investigated if PINK1 and Parkin confer neuroprotection against ischemia through PINK1/Parkin MQC pathways. However, I did not find any evidence indicating Parkin mitochondrial translocation following stroke insult suggesting that PINK1/Parkin MQC pathways are not involved in the protective functions of PINK1/Parkin. Interestingly, I found that PINK1 or Parkin deficiency decreases the level of phosphorylation of pro-survival protein AKT (pAKT) whereas expression of these genes enhances pAKT following glutamate treatment. My data also indicate that the mTORC2/AKT pathway partially mediates the neuroprotective effect of PINK1. Taken together, my data indicate that both PINK1 and Parkin play a critical neuroprotective role against ischemia and Ca2+ dysregulation in a fashion independent of mitochondrial control but dependent on AKT function.
Keywords: Parkinson's disease; PINK1; Ischemia; Stroke; Parkin